Law Enforcement of Thrifting Practices Through Overseas Online Thrift Shops with Instagram Applications - Nur Aziah Eka Putri; Ratna Kartika Wati (Publikasi Indonesia, 2024)
Technology has changed people's habits, including the way they buy things. Thrifting can be a way for fashion lovers or fashionistas to learn about trends so that they can find very varied and unexpected clothing models. In the implementation of thrifting, there are currently many platforms that can be used online. The most commonly used online platforms are Instagram, TikTok, shopee, and many other e-commerce. This article aims to discuss the mechanism of online thrifting through the Instagram application and to examine law enforcement against the practice of Thrifting through the Instagram application. The result of this research is that the impact of the online thrifting mechanism using the Instagram application hurts security in customs supervision and threatens local industries. The practice of thrifting carried out online utilizes loopholes in supervision and regulation so that many business actors can still sell imported used goods illegally. To address this issue, cooperative action is needed between the government, social media platforms, and the public. The government needs to strengthen regulations and improve oversight of online buying and selling activities, including working with platforms like Instagram to identify and crack down on unlawful accounts.